Some antioxidants and malondialdehyde levels in the flesh of rainbow trout,(Oncorhynchus mykiss W., 1792) from various feeding habitats - Ural, Mevlüt Şener; Karataş, Fikret; Çalta, Metin (My University, 2015)
The present study was aimed to find the effect of feeding habitats on the amounts of some antioxidants (vitamin A, E, C, ß-carotene and selenium) and malondialdehyde (MDA) levels in the flesh of rainbow trout (Oncorhynchus mykiss). For this purpose, vitamins (A, C and E), ?-carotene amounts and malondialdehyde (MDA) levels were determined by HPLC and selenium amount was determined by fluorometric method in the flesh of rainbow trout obtained from various feeding habitats. The highest amounts of vitamins (A, C and E), ?-carotene and selenium were found in the flesh of wild rainbow trout (WRT), followed by cage reared rainbow trout (CRRT) and pond reared rainbow trout (PRRT). However, the levels of MDA in the flesh of PRRT were the highest, followed by CRRT and the lowest in WRT.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Rainbow trout; Oncorhynchus mykiss; Euphrates river; Vitamins; ?-carotene; Selenium